Mekanisme dan Implementasi Pengelolaan Dana Pensiun Syariah Terhadap Fatwa DSN-MUI Nomor 88/DSN-MUI/XI/2013 pada Bank Syariah Indonesia Cabang Gresik - Walid In'am Ahmad; Muhammad Yazid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the mechanism and implementation of sharia pension fund management against the DSN MUI fatwa number 88 DSN MUI XI in 2013 where the object of the study was conducted at Bank Syariah Indonesia, Gresik branch. The study uses a descriptive qualitative research type where this study functions to provide a direct explanation of the phenomenon being studied using data obtained directly from the research object being studied. This study in conducting data analysis uses the Miles and Hubberman method, namely data reduction then continued with data presentation and ended with drawing conclusions. This study was taken using secondary data where the source of information provided came from the official website of Bank Syariah Indonesia and also various journals and references related to the title of the study. The results of this study are intended to determine how the mechanism and implementation of the management of sharia pension funds against the DSN MUI fatwa number 88 DSN MUI XI in 2013 at the BSI Gresik branch where in the management process it avoids gharar, maysir and also usury and remains in accordance with Islamic principles for the mechanism itself is divided into 7 parts including sharia contracts, fundraising, sharia investment, distribution of investment results, risk management, disbursement of pension funds and the last is compliance and supervision of sharia in BSI products that are related to sharia pension funds is BSI berkah where this product is a creation of Bank Syariah Indonesia in assisting customers to prepare pension funds while remaining compliant with sharia principles